Purinergic neurone-glia signalling in cognitive-related pathologies. (May 2016) - Illes, Peter; Verkhratsky, Alexei
Abstract: Neuroglia, represented by astrocytes, oligodendrocytes, NG glia and microglia are homeostatic, myelinating and defensive cells of the brain. Neuroglial cells express various combinations of purinoceptors, which contribute to multiple intercellular signalling pathways in the healthy and diseased nervous system. Neurological diseases are invariably associated with profound neuroglial remodelling, which is manifest by reactive gliosis, pathological remodelling and functional atrophy of various types of glial cells. Gliopathology is disease and region specific and produces multiple glial phenotypes that may be neuroprotective or neurotoxic. In this review we summarise recent knowledge on the role of glial purinergic signalling in cognitive-related neurological diseases. This article is part of the Special Issue entitled 'Purines in Neurodegeneration and Neuroregeneration'. Graphical abstract: Highlights: Neuroglia is fundamental for evolution of all neurological disorders. Neurons and glial cells interact with each other using various signalling molecules. Purinergic signalling system contributes to pathogenesis of multiple cognitive-related neuropathologies.